Organizational Culture in Waste Collection Fleet Management: Implications for Operational Efficiency and Urban Environmental Impact - Ardiyanti Ardiyanti; Achmad Husen; Dian Alfia Purwandari; Arradina Zessa Devy; Nurcitra Rehulina Br Ginting (Publikasi Indonesia, 2025)
Waste collection fleets play a vital role in municipal solid waste management and urban environmental quality. Nevertheless, operational inefficiencies, such as vehicle overloading, suboptimal route planning, and inadequate maintenance, have contributed to significant environmental and infrastructural impacts, including road degradation and diminished urban hygiene. This research adopts a qualitative approach grounded in a comprehensive review of relevant literature to examine how organizational culture affects the performance of waste collection fleets and their broader urban impact. The findings suggest that weak institutional culture, fragmented coordination among agencies, and inconsistent adherence to operational standards are critical drivers of inefficiency. Moreover, limited inter-agency integration, the absence of effective oversight mechanisms, as well as limited technological innovation further compound these challenges. Addressing these systemic issues requires targeted cultural and governance reforms. Key recommendations include strengthening human resource capacity, integrating environmentally sound technologies, and fostering institutional accountability and environmental responsibility. These interventions are essential to enhance operational efficiency. They also play a key role in reducing the ecological footprint of urban waste transportation systems.